Electrochemical analysis of 5-Nitro-2-furaldehyde semicarbazone as a mild steel corrosion inhibitor in corrosive solution: An EIS, adsorption and SEM study - Dalia M. Jamil; H.S. Aljibori; Ahmed Alamiery (Results in Chemistry)
The results obtained from EIS, weight loss measurements, adsorption isotherms, and SEM were used to investigate the electrochemical behavior of NFS as a corrosion inhibitor for mild steel in 1.0 M HCl. The inhibition efficiency of NFS the electrode reaction was found to increase with NFS concentration up to a maximum value of 0.5 mM with 92.1 % inhibition efficiency, based on mass loss measurements. The findings revealed that the inhibitive performance of the investigated inhibitor was slightly higher at higher temperatures, indicating improved better protection at elevated thermal conditions. Based on the analysis of the adsorption isotherm studies on mild steel, the findings revealed that the adsorption of NFS can be follows the Langmuir isotherm model, although both chemisorption and physisorption mechanisms were observed. Analysis of the surface morphology by SEM also showed a smooth and resistant surface with less corrosion when NFS is present consistent with previous findings of NFS as a corrosion inhibitor. The inhibition mechanism was further explained in more detail and has given a good understanding regarding the behavior of NFS molecules and steel surface. Therefore, the results demonstrated in this work show that NFS has the potential for acting as a protective barrier against the steel corrosion in corrosive solution.